Fashion orientation, shopping mall environment, and patronage intentions: A study of female fashion shoppers - Michon, Richard; Chebat, Jean-Charles; Yu, Hong; Lemarie, Linda (My University, 2015)
The purpose of this paper is to explore female fashion shoppers’ perception and response to the mall environment. Specific objectives include a conceptual model of female fashion shoppers’ experience in a mall environment incorporating fashion orientation, store personality, shopping mall perception, shopping value, and patronage intentions.
Keywords: Fashion retailing; Consumer perception; Hedonism; Shopping; Shopping mall; Utilitarianism